THE STUDY OF THE PROPERTIES OF VULCANIZATES BASED ON ETHYLENE VINYL ACETATE RUBBERS WITH DIFFERENT CONTENT OF VINYL ACETATE UNITS - M. V. Syayleva; A. M. Bukanov; K. A. Zvezdenkov; V. N. Voloshin (Тонкие химические технологии, 2018)
The article studies the structure and properties of ethylene vinyl acetate rubbers and the influence of the vinyl acetate (VA) units content in the rubber on the technological, physical-mechanical, operating and electrical properties of vulcanizates. The results of the study prove that the distinctive feature of ethylene vinyl acetate rubbers compared to other rubbers is their thermoplastic properties and low viscosity. Besides, the high resistance to ozone, heat and oil resistance and good mechanical properties of vulcanizates based on them make this type of polymer materials very promising for the creation of modern products. It is shown that the values of elasticity modulus, strength, elongation and tear resistance are increased with increasing VA units content in the rubber. Besides, swelling in hydrocarbon media decreases. Vulcanizates containing 40-45% of VA have satisfactory electrical characteristics and good moisture resistance and can be used as the base insulating rubber. Vulcanizates with a high content of vinyl acetate units (60-70%) have high oil and heat resistance. Therefore, their use in rubber compounds for cable jackets is most effective. The study of the properties of ethylene vinyl acetate rubbers and their vulcanizates allowed to develop formulations of insulating and jacket rubbers and to determine the most promising areas of their application for modern cable products of special purpose in the petrochemical, aerospace, transport and shipbuilding industries.